Factors influencing the occurrence of neck pain complaints in garment convection tailors - Siregar, Damayanti; Handoko, Ellya Keriahen; Setiawan, Deni; Sembiring, Sindy Boru; Yumardika, Deza; Renaldi, Muhammad Rizal; Pane, Herlin Novita; Tanjung, Fahrul Azmi; Siahaan, Nelly Christina; Mylano, Tri Adi; Nur, Putri Amriany (Buletin Kedokteran & Kesehatan Prima, 2025)
This study aimed to identify the factors influencing neck pain complaints among garment convection tailors in Medan City. A total of 44 tailors from a convection workshop on Jl. Denai were included as the study's population and sample, utilizing a total sampling technique. The research employed a cross-sectional analytical survey design with data analysis using the Chi-Square test. The findings from the bivariate analysis showed a significant association between neck pain complaints and three key factors: years of service (p=0.021), work duration (p=0.044), and work posture (p=0.000). Specifically, a higher percentage of severe neck pain was found in workers with fewer years of service and longer work durations (more than 8 hours a day). The analysis also revealed that age (p=0.717) and lighting (p=0.062) were not statistically significant factors. A subsequent multivariate analysis identified work posture and work duration as independent factors influencing neck pain, with work posture being the most dominant variable (p=0.000). The multivariate analysis for work posture had an odds ratio of 64.346, indicating a strong positive correlation with severe neck pain. However, a contradictory result for work duration in the multivariate analysis suggested a need for re-examination of its coding. The study concludes that workload, work duration, and working posture are the primary factors influencing neck pain complaints in convection tailors, with work posture being the most dominant. These findings highlight the importance of ergonomic interventions, proper posture, and regulated work hours to mitigate occupational health risks in this population.